PELAKSANAAN PREGNANCY NURSING TERPADU PADA IBU HAMIL DAN CONTINUITY OF CARE PADA NEONATUS DI KLINIK MADINAH MEDAN - HALIMAH, Halimatussakdiyah Lubis; Yusnaini; Fika Lestari (MULIA (Jurnal Pengabdian kepada Masyarakat), 2023)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still the main problems in Indonesia's health development. AKI or Maternal Mortality Rate (MMR) is an indicator of women's health level that describes the level of access, integrity, and effectiveness of the health sector. Therefore MMR is used as an indicator of the level of welfare of a country. Ministry of Health, 2015). The goal of midwifery services for pregnant women is to get integrated and comprehensive services according to standards, should make at least six visits during the antenatal period, namely one visit during the first trimester, once during the second trimester, and twice during the third trimester, as well as two visits to specialists. pregnancy in the first and third trimesters. It is necessary to immediately check the pregnancy if there is a disturbance or if the fetus does not move for more than 12 hours (Rachman, 2021). Efforts made by the government to reduce IMR include: (a) improving Neonatal health services, namely by requiring that every newborn receive Neonatal Visit services at least 3 times (KN1, KN2, and KN3) according to standards.